Non-invasive assessment of short and ultra-short heart rate variability during different physical and physiological tests (Kinesiology, 2021)
The main aim of the present study was to determine the short- and ultra-short-term heart rate variability (HRV) during different physical and physiological tests and to compare HRV to different performance levels. The latter aim was to compare participants’ short- and ultra-short-term heart rate variability before-duringpost- tests. Our hypothesis was that there would be a significant difference between test performance and HRV parameters, and the high performing group would have significantly higher HRV parameters than the low performing group. Fifty-three healthy men (Mage=26.9±4 years, Mheight=177.9±5.7 cm; Mweight=77.8±8.7 kg) were recruited in the current study. We completed the data collection procedure for each participant in four consecutive days. On day-1, anthropometric measurements were conducted and then participants performed isokinetic tests. On day-2, participants performed anaerobic tests; on day-3 equilibrium tests, and on day-4 aerobic capacity tests. The HRV records of all participants were obtained before, during and after all these tests. Based on the participants’ performance, they were divided into two groups: participants in G1 had lower performance and those in G2 higher performance. A two-way repeated measures ANOVA yielded significant differences in HRV values obtained in the four different tests. There was a significant difference between fitness test performance and the variation of short- and ultra-short-term HRV parameters. Also, significant differences in HRV values before, during, and after the testing were observed.Key words: autonomic nervous system, heart rate variability, physical and physiological tests